A STUDY OF MISINFORMATION EXPOSURE OF COVID-19 VACCINE AND THE WILLINGNESS TO BE VACCINATED IN TANGERANG SELATAN CITY, INDONESIA - Raihana Nadra Alkaff; Narila Mutia Nasir; Dela Aristi; Jihan Fadilah Faiz (Jurnal Kesehatan Reproduksi, 2021)
Abstract Latar Belakang: Vaksin COVID-19 sangat penting dalam upaya mengurangi penyebaran penularan. Namun, penolakan terhadap vaksin yang terjadi mungkin disebabkan oleh beredarnya misinformasi tentang vaksin COVID-19 melalui media sosial. Tujuan: Penelitian ini bertujuan untuk mengkaji paparan misinformasi vaksin COVID-19 dan faktor-faktor yang terkait serta mengidentifikasi hubungan antara paparan misinformasi vaksin COVID-19 dengan keinginan untuk divaksinasi. Metode: Studi potong lintang dilakukan pada orang berusia 18-34 tahun di Kota Tangerang Selatan. Dengan menggunakan metode convenience sampling, kami merekrut 227 responden yang mengisi kuesioner secara online melalui google form. Data dianalisis menggunakan uji chi-square, uji Fisher, dan regresi logistik. Hasil: Responden yang tidak memiliki kuota internet cenderung 2,197 kali untuk terpapar misinformasi. Responden yang temannya tidak peduli jika mereka menyebarkan misinformasi memiliki kemungkinan 2.1 kali lebih besar untuk mendapatkan misinformasi. Responden yang memiliki teman yang menyebarkan misinformasi cenderung 1,9 kali lebih besar untuk terpapar misinformasi. Studi ini tidak menemukan hubungan yang signifikan antara paparan misinformasi COVID-19 dan kesediaan untuk divaksinasi. Kesimpulan: Pengaruh teman sebaya terkait paparan misinformasi vaksin COVID-19 sangat penting. Pengembangan model pendidik sebaya sangat penting untuk mendorong kontribusi kaum muda dalam mengakhiri pandemi. Kata kunci: Misinformasi, Vaksin COVID-19, kaum muda, Teman Sebaya, Indonesia Abstrak Background: COVID-19 vaccine is important to reduce the spread of transmission. However, the objection occurred might be caused by the circulation of misinformation of COVID-19 vaccine through social media. Objective: This study aimed to assess the misinformation exposure of COVID-19 vaccine and its related factors and to identify the association between misinformation exposure of COVID-19 vaccine and the willingness to be vaccinated. Method: A cross-sectional study was conducted on people age 18-34 years in Tangerang Selatan City. Using convenience sampling, we recruited 227 respondents who filled an online questionnaire through a google form. Data were analyzed using the chi-square test, fisher’s exact test, and logistic regression. Result: Respondents who did not have sufficient internet balance were 2.197 more likely to have misinformation exposure. Respondents whose friends were ignorant if they spread misinformation were 2.1 times more likely to get misinformation. Respondents whose friends disseminated misinformation were 1.9 times more likely to get exposed to misinformation of the COVID-19. This study found no significant relationship between misinformation exposure of COVID-19 vaccine and willingness to be vaccinated. Conclusion: Peer influence regarding exposure to COVID-19 vaccine misinformation is very important. Developing a peer educator model is prominent to encourage the role of young people to end the pandemic. Keywords: Misinformation, COVID-19 Vaccine, Young People, Peer, Indonesia